Functional Roles of Branched-Chain Amino Acids in Poultry Nutrition and Health: A Review - Mohamed , Mohammed Hasib; Jasim , Ruya. F. (American Journal of Biodiversity, 2025)
We reviewed the physiological/functional roles of BCAAs (i.e. leucine, isoleucine and valine) in poultry and poultry health in the present review. As such, BCAA is a substrate for protein synthesis as well as an anabolic regulator and acts also as a systemic metabolic/physiological modulator. This also explains the improvement in broiler growth performance, feed efficiency as well as carcass traits and egg production and quality of laying hens as a result of dietary supplementation with BCAAs. Furthermore, BCATs are important for functions such as immunity, gut health, and microbiota homeostasis, and they reduce adverse effects of heat stress or oxidative stress perturbations. But, if the ratios are unbalanced or further accompanied with high leucine content, antagonistic effects are probable and they may negatively impact performance. The paper articulates opportunities for the precision feeding, the assignment of nanoencapsulation technology and genetic approach to enhance the utilization of BCAAs are described for the sustainable poultry production.